Potential Role of CXCL10 in Monitoring Response to Treatment in Leprosy Patients - Ferreira, Helen; Mendes, Mayara Abud; de Mattos Barbosa, Mayara Garcia; de Oliveira, Eliane Barbosa; Sales, Anna Maria; Moraes, Milton Ozório; Sarno, Euzenir Nunes; Pinheiro, Roberta Olmo (Frontiers in Immunology, 2021)
The treatment of multibacillary cases of leprosy with multidrug therapy (MDT) comprises 12 doses of a combination of rifampicin, dapsone and clofazimine. Previous studies have described the immunological phenotypic pattern in skin lesions in multibacillary patients. Here, we evaluated the effect of MDT on skin cell phenotype and on the Mycobacterium leprae-specific immune response. An analysis of skin cell phenotype demonstrated a significant decrease in MRS1 (SR-A), CXCL10 (IP-10) and IFNG (IFN-γ) gene and protein expression after MDT release. Patients were randomized according to whether they experienced a reduction in bacillary load after MDT. A reduction in CXCL10 (IP-10) in sera was associated with the absence of a reduction in the bacillary load at release. Although IFN-γ production in response to M. leprae was not affected by MDT, CXCL10 (IP-10) levels in response to M. leprae increased in cells from patients who experienced a reduction in bacillary load after treatment. Together, our results suggest that CXCL10 (IP-10) may be a good marker for monitoring treatment efficacy in multibacillary patients.